(untitled) (Global Journal of Management and Business Research, 2017)
The current study aimed at investigating the marketing managers’ degrees of awareness about the significance of customer experience management (CEM) in the Jordanian banking, insurance, and financial services sectors. The researchers designed a questionnaire and then they distributed the questionnaire forms to the selected sample. The overall response rate is (77.419 %) to include forty eight (48) marketing managers, thirteen (13) of them were working in Jordanian banks, nineteen (19) of them were working in Jordanian insurance companies, and thirty (30) of them were working in companies that provide customers with financial services. After analyzing the collected data statistically, the researchers concluded that marketing managers displayed high degrees of awareness in the significance of customer experience management (CEM) in the Jordanian banking, insurance, and financial services sectors.